The adverse selection problem in imperfectly competitive credit markets - Ville Mälkönen; Timo Vesala (Bank of Finland, 2006)
We study the adverse selection problem in imperfectly competitive credit markets and illustrate the circumstances where a separating equilibrium emerges, even without collateral.The borrowers are heterogeneous in their preferences concerning the banks.Separation obtains in market segments where the 'high risk' borrowers receive credit from their preferred bank.The 'low risk' borrowers choose the ex-ante less-preferred bank that offers loan contracts with lower interest rates.The availability of credit will be maximized under an intermediate level of competition, a prediction that is supported by recent empirical evidence.
URN:NBN:fi:bof-20140807113
Keywords: D43; D82; G21; L13; 330; asymmetric information; credit rationing; bank differentiation